Secondhand smoke increases the risk of developing chronic obstructive pulmonary disease - Wen-Chi Su; Huai-Lei Juan; Jia-In Lee; Shu-Pin Huang; Szu-Chia Chen; Jiun-Hung Geng (Scientific Reports, 2024)
Abstract Smoking is the most important risk factor for chronic obstructive pulmonary disease (COPD), however evidence from large-scale studies on whether secondhand smoke (SHS) increases the risk of COPD is still lacking. We conducted this large longitudinal study to investigate the association between SHS and the development of COPD. This is a longitudinal study. Data on 6519 subjects who were never-smokers, had no history of COPD, and had complete lung function records were extracted from the Taiwan Biobank. They were divided into two groups according to SHS exposure: no exposure and exposure groups. Data were collected when participants enrolled in the study and during regular follow-up. Cox proportional hazards regression models were used to estimate the relative risk (RR) and 95% confidence interval (CI) for the association between SHS and the risk of developing COPD. At 48 months of follow-up, 260 (4%) participants in the no exposure group and 34 (7%) participants in the exposure group developed COPD. The RR of incident COPD development was significantly higher in the exposure group than that in the no exposure group after adjusting for confounders (RR = 1.49; 95% CI 1.04 to 2.14; P value = 0.031). There is a dose–response relationship between the duration of exposure to SHS and the risk of incident COPD, which demonstrates that an additional hour of exposure to SHS per week was associated with a 1.03-fold increased likelihood of developing COPD after adjusting for confounders (RR = 1.03; 95% CI 1.00 to 1.05; P value = 0.027). SHS exposure contributes to the development of COPD. This finding can help raise awareness of the harms of SHS and provide a reference for formulating anti-smoking policies.